The effects of feeding dry distiller’s grains with solubles on ruminal metabolism, growth performance, and carcass traits of feedlot cattle - Uwituze, Solange (Kansas State University, 2008)
Three trials were conducted using dried distiller's grains with solubles (DDGS) to evaluate effects on feedlot performance, carcass characteristics, ruminal fermentation, and diet digestibility in cattle fed steam-flaked corn-based diets. In trial 1, crossbred yearling heifers were used in a finishing trial to evaluate interactions between corn-DDGS feeding levels and roughage source (alfalfa hay vs corn silage) in terms of impact on feedlot performance and carcass characteristics. Experimental diets were based on steam-flaked corn and contained 0% DDGS with 6% alfalfa hay (AH), 0% DDGS with 10% corn silage (CS), 25% DDGS with 6% AH, or 25% DDGS with 10% CS (DM basis). Results indicated no interaction between levels of DDGS and roughage source. Heifers fed DDGS as a partial replacement for steam-flaked corn had similar growth performance and carcass merit compared to heifers fed diets without DDGS. Corn silage and alfalfa hay were comparable roughages when a portion of steam-flaked corn was replaced with DDGS. The second trial was a companion metabolism study in which ruminal fermentation characteristics and diet digestibility were examined in 12 cannulated Holstein steers fed steam-flaked corn finishing diets with or without DDGS, using alfalfa hay or corn silage as roughage sources. Diets were similar to those fed in the performance study and consisted of steam-flaked corn with 0 or 25% DDGS (DM basis) and 6% AH or 10% CS (DM basis). Feeding DDGS decreased ruminal pH and ruminal ammonia concentrations, and digestion of DM and OM were less compared to diets without DDGS. The decrease in digestibility was largely attributable to poorer digestion of CP and, to a lesser extent, a reduction in starch digestion. The third study was designed to investigate effects of pH (5.0, 5.5, and 6.0) on in vitro fermentative activity by ruminal microorganisms from cattle adapted to a finishing diet containing 25% DDGS (DM basis). Higher pH led to greater dry matter disappearance in vitro (P < 0.01). DDGS can be an effective substitute for steam-flaked corn. Efforts to address low ruminal pH and low ruminal ammonia may prove beneficial for improving value of DDGS as cattle feed.
Keywords: Distiller's grains; Ruminal metabolism; Ruminal pH; Digestibility; Feedlot cattle; Growth performance; Agriculture, Animal Culture and Nutrition (0475)